Heparin prevents Zika virus induced-cytopathic effects in human neural progenitor cells - Ghezzi, Silvia; Cooper, Lynsay; Rubio, Alicia; Pagani, Isabel; Capobianchi, Maria Rosaria; Ippolito, Giuseppe; Pelletier, Julien [UNESP]; Meneghetti, Maria Cecilia Z.; Lima, Marcelo A.; Skidmore, Mark A.; Broccoli, Vania; Yates, Edwin A.; et al. (Elsevier B.V., 2017)
The recent Zika virus (ZIKV) outbreak, which mainly affected Brazil and neighbouring states, demonstrated the paucity of information concerning the epidemiology of several flaviruses, but also highlighted the lack of available agents with which to treat such emerging diseases. Here, we show that heparin, a widely used anticoagulant, while exerting a modest inhibitory effect on Zika Virus replication, fully prevents virus-induced cell death of human neural progenitor cells (NPCs). (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Zika virus (ZIKV); Neural progenitor cells; Heparin; Cell death